Endovascular Treatment with GDC for Severe Acute SAH: Comparison with Early Direct Surgery - Kobayashi, S. (Centauro S.r.l., 2000)
The purpose of this study was to evaluate the effect of endovascular treatment with Guglielmi detachable coils (GDC) on the outcome of severe subarachnoid hemorrhage (SAH) caused by acute rupture of a cerebral aneurysm and on the incidence of symptomatic vasospasm. Thirty-five patients with aneurysmal SAH were treated in the acute stage using GDC. Fifteen out of 17patients in Hunt & Kosnik grades I, II, and III showed good recovery (GR) at discharge, while one was moderately disabled (MD) and one was severely disabled (SD). Among 16 patients in poor neurological condition (GCS was ≤ 9 on admission), the outcome was GR in 5 cases (31%), MD in 2 (13%), and SD in 9 (56%). These results were better than those for surgically treated patients with the same neurological status. The difference in outcome between endovascular treatment and surgery may have been related to the difference in the insult to the brain caused by each modality. The incidence of symptomatic vasospasm was lower in the GDC group (5.7%) than in the surgical group (12%). In the patients treated with GDC and intrathecal administration of urokinase, subarachnoid clots were cleared more rapidly than in those treated surgically with continuous cisternal irrigation. The accelerated clearance of subarachnoid clots in the GDC group might have helped to prevent delayed vasospasm. The long-term efficacy of GDC embolization in preventing subsequent bleeding has not yet been determined. However, this method seems to be less traumatic for the brain and may be suitable for treatment of patients with severe SAH.